Experimental Analysis of Facebook Marketing Using Conjoint Analysis and Eye Scanning - Hildur Einarsdóttir 1985- (2013)
The main objective of the study is to understand how different attributes, presented in the online Facebook environment, affects the consumer’s perception towards displayed item and the likelihood of purchase. To achieve the objectives, two studies were conducted. First study involved identifying the most important attributes influencing the online purchase using conjoint analysis. Second study involved taking the attributes obtained from the conjoint study and applying it into real life setting and analyse them using Tobii 1750 eye scanner device. Participants in both studies were students at Reykjavik University. Results from study 1 showed that price has the most motivational impact on the participant’s likelihood of purchasing item online. Results from study 2 showed that if pricing is presented with a model in the picture, the model takes fixation time away from the price. Placement of the price is more efficient located in the picture in bold, black letters, with red box around it. Placement of the price under likes and comments is less efficient. The current research was conducted in collaboration with Manía, a fashion store in Reykjavík Iceland, and MMR Icelandic marketing and disseminate research company. Meginmarkmið rannsóknarinnar var að skoða hvernig mismunandi eiginleikar, sem settir eru fram með vöru á Facebook, hafi áhrif á skynjun og túlkun kaupenda gagnvart vörunni og auki líkur á kauphegðun neytenda. Til að öðlast skilning á þessu voru framkvæmdar tvær mismunandi rannsóknir. Fyrri rannsóknin var framkvæmd til að bera kennsl á hvaða eiginleikar það eru sem auka líkur á að varan sé keypt í gegnum netið. Seinni rannsóknin var byggð á niðurstöðum úr fyrri rannsókninni og sett í raunverulegt samhengi með augnskanna rannsókn þar sem notast var við Tobii 1750 augnskanna. Þátttakendur í báðum rannsóknum voru nemendur við Háskólann í Reykjavík. Niðurstöður fyrri rannsóknar voru þær að sá eiginleiki sem þótti mest líklegur til að hafa áhrif á kauphegðun neytenda var verð vörunnar. Niðurstöður seinni ...